INFLATION VS. UNEMPLOYMENT - SOME POLEMIC ISSUES - Lisý, Ján; Muchová, Eva (European Scientific Journal, ESJ, 2014)
The relationship between the rate of inflation and the rate of unemployment is one of the most discussed macroeconomic issues in economic theory and business practice. A. W. Phillips published in 1958 his pioneering article and for the first time pointed to this relationship. Later the issue was addressed by other prominent economists: P. Samuelson, R. Solow, M. Friedman and E. Phelps. The original Phillips curve, as a part of the Keynesian theory instruments, formed the basis of Keynesian economic policy. The monetarist interpretation of Phillips curve is based on so-called natural rate of unemployment and inflation expectations. Currently there are turbulent debates, often contradictory and conflicting, under way over the validity of the Phillips curve and over the various factors that affect the relationship between unemployment and inflation. The paper deals with the polemic issues of mutual relationship between unemployment and inflation and presents European perspectives as well. Both inflation and unemployment belongs to the convergence criteria relevant for a successful monetary union. Eurozone countries have relevantly different trends in the competitive position due to different inflation and wage growth.